Evaluation of spring herbicide programs during a three-year sugarcane (Saccharum spp. hybrids) cropping cycle - Alice A. Wright; Douglas J. Spaunhorst; Eric Petrie (Weed Technology)
A limited number of herbicides and sites of action are registered for use on sugarcane in Louisiana. Repeated use of the same sites of action can lead to the evolution of herbicide resistance by weeds. Therefore, it is critically necessary to evaluate additional sites of action to provide growers with options for rotating herbicides to reduce the risk of resistance. Topramezone, indaziflam, and a formulation that includes mesotrione, bicyclopyrone, atrazine, and S-metolachlor, along with more common herbicides (pendimethalin, and metribuzin, clomazone, and diuron), were evaluated in the spring for injury to sugarcane, weed control, sugarcane yield, and sugar yield. Of these treatments, clomazone applied with diuron was the only herbicide combination to consistently injure the crop, with injury estimates ranging from 11% to 36%, which frequently resulted in reduced sugar yield with losses between 2.3% to 24.1% of the nontreated control. In most treatments, an increase in itchgrass counts was observed between harvests, indicating that additional control strategies will be needed in fields infested with this weed. However, topramezone alone and with triclopyr was well tolerated by sugarcane, with injuries ranging from 0% to 11% 2 wk after treatment. Indaziflam and combined application of mesotrione, bicyclopyrone, atrazine, and S-metolachlor injury was at or under 10% 2 wk after treatment. The tolerance of sugarcane for these herbicides suggests that they can be incorporated into weed management strategies in sugarcane production. These herbicides would increase the sites of action available to be applied to sugarcane and help mitigate the risk of herbicide-resistant weeds.